Reading the world: English-language literatures as a tool for fostering critical language awareness - J. Lo Bello, Maya (Gyermeknevelés Tudományos Folyóirat, 2023)
This paper summarises how a critical pedagogical approach was joined with community-based action research to foster a critical language awareness (CLA) perspective in redesigning and implementing the course, Practice in communicating English literature. Held at Eötvös Loránd University’s Faculty of Primary and Pre-School Education (ELTE TÓK) as a part of the English specialisation programme in bilingual education for pre-service primary teachers, the curriculum used for teaching this course originally emphasised literary history, canonical works, chronological order, and literacy, all earmarks of the kind of literature pedagogy most commonly employed in Hungarian classrooms. The questions investigated in this research therefore examine whether students socialised in the literature pedagogy methods listed above would react positively to unfamiliar materials and practices; whether literature could promote language learning in a way that emphasises content over literacy; and whether literature could motivate adult language learners to become autonomous language users who possess their own, English-language identity. The example of the first known, English-language autobiography, The Book of Margery Kempe (1501/1985), will provide a set of practices (including storytelling, creative writing, role play and debate) for promoting critical language awareness among pre-service primary teachers. Redefining the aims and material for Practice in communicating English literature demanded further investigation in affirming its effectiveness while assessing the need to expose students to a broader range of cultural influences. The qualitative methods of document/coursebook analysis, observation, and a questionnaire conducted with students provide further input in determining whether the selected curriculum promotes CLA and Krachu’s definition of world Englishes (1996).